Efficacy, safety and patient-reported outcomes of combination etanercept and sulfasalazine versus etanercept alone in patients with rheumatoid arthritis: a double-blind randomised 2-year study. Issue 7 (15th September 2008) - Combe, B; Codreanu, C; Fiocco, U; Gaubitz, M; Geusens, P P; Kvien, T K; Pavelka, K; Sambrook, P N; Smolen, J S; Khandker, R; Singh, A; Wajdula, J; et al.
Abstract : Objective: To determine the efficacy and safety of etanercept and etanercept plus sulfasalazine versus sulfasalazine in patients with rheumatoid arthritis (RA) despite sulfasalazine therapy. Methods: Patients were randomly assigned to etanercept (25 mg twice weekly; sulfasalazine was discontinued at baseline), etanercept plus sulfasalazine (unchanged regimen of 2–3 g/day) or sulfasalazine in a double-blind, randomised, 2-year study in adult patients with active RA despite sulfasalazine therapy. Efficacy was assessed using the American College of Rheumatology criteria, disease activity scores (DAS) and patient-reported outcomes (PRO). Results: Demographic variables and baseline disease characteristics were comparable among treatment groups; mean DAS 5.1, 5.2 and 5.1 for etanercept (n = 103), etanercept plus sulfasalazine (n = 101) and sulfasalazine (n = 50), respectively. Withdrawal due to lack of efficacy was highest with sulfasalazine (26 (52%) vs 6 (6%) for either etanercept group, p<0.001). Patients receiving etanercept or etanercept plus sulfasalazine had a more rapid initial response, which was sustained at 2 years, than those receiving sulfasalazine: mean DAS 2.8, 2.5 versus 4.5, respectively (p<0.05); ACR 20 response was achieved by 67%, 77% versus 34% of patients, respectively (p<0.01) Overall, PRO followed a similar pattern; a clinically significant improvement in health assessment questionnaire was achieved by 76%, 78% versus 40% of patients, respectively (p<0.01). Commonly reported adverse events occurring in the etanercept groups were injection site reactions and pharyngitis/laryngitis (p<0.01). Conclusion: Etanercept and etanercept plus sulfasalazine are efficacious for the long-term management of patients with RA. The addition of etanercept or substitution with etanercept should be considered as treatment options for patients not adequately responding to sulfasalazine.